Tomato peel (solanum lycopersicum l.) colonization by the endophyte yeast candida guilliermondii (castellani) langeron et guerra (2012)
During the postharvest period, fruits are lost due to attack by phytopathogens and incorrect storage and manipulation. The use of yeasts has been presented as one of the most promising strategies to resolve some of these problems. This research standardized a methodology to study, under controlled conditions, the colonization of the epidermis and subepidermal region of tomato fruit by the yeast Candida guilliermondii. In addition, it determined the path of yeast distribution from histological sections in tissues within 70 hours after inoculation. The results showed that C. guilliermondii is an endophytic yeast capable of entering through the healthy cuticle of ripe tomato fruits and colonizing apoplastic spaces without causing damage to plant tissues. The dynamics of colonization were established during the first 70 hours and the speed of yeast migration into the fruit was estimated at 0.55 μm hour-1.